Pengaruh Model Problem Based Learning (PBL) terhadap Hasil Belajar Kognitif IPAS Tema Pelestarian Lingkungan Kelas IV UPTD SDN Demangan 1 Bangkalan - Widiyah Dwi Wulan Sari; Humairah Fauziah (Mataram University, 2026)
This study aimed to examine the effect of the Problem-Based Learning (PBL) model on students’ cognitive learning outcomes in Science and Social Studies (IPAS) on the topic of Environmental Conservation among fourth-grade students at UPTD SDN Demangan 1 Bangkalan. IPAS learning in elementary schools is still largely dominated by lecture-based instruction with limited use of learning media, resulting in teacher-centered learning and suboptimal cognitive learning outcomes. This study employed a quantitative approach using a pre-experimental method with a one-group pretest–posttest design. The sample consisted of 36 fourth-grade students in class IV-A. Data were collected through tests, observations, and questionnaires. The test instrument was examined for validity, reliability, item difficulty, and discrimination index. Data were analyzed using the Shapiro–Wilk normality test and the Wilcoxon Signed Rank Test. The results showed a Z value of −5.130 and an Asymp. Sig. (2-tailed) value of < 0.001, which was lower than the significance level of 0.05. Therefore, the null hypothesis (H₀) was rejected and the alternative hypothesis (Hₐ) was accepted. These findings indicate that the implementation of the Problem-Based Learning (PBL) model had a significant positive effect on students’ cognitive learning outcomes in IPAS.